Durvalumab as consolidation therapy in patients who received chemoradiotherapy for unresectable stage III NSCLC: Real-world data from an expanded access program in Brazil (LACOG 0120) - Mauro Zukin; Victor Gondim; Andrea Kazumi Shimada; Ellias Magalhães e Abreu Lima; Clarissa Mathias; Williams Fernandes Barra; William Nassib William Junior; Mônica Padoan; Yuri Bittencourt; Rosely Yamamura; Carlos Eduardo Baston Silva; Letícia de Jesus Rossato; et al. (Jornal Brasileiro de Pneumologia)
ABSTRACT Objective: The PACIFIC trial established standard therapy for patients with unresectable stage III NSCLC who did not progress after platinum-based concurrent chemoradiation therapy. However, real-world data, particularly from Latin America, remain limited. The LACOG 0120 study aimed to evaluate the efficacy and safety of consolidation therapy with durvalumab in a real-world setting in Brazil. Methods: Patients with unresectable stage III NSCLC who received chemoradiotherapy followed by durvalumab consolidation therapy through an expanded access program were evaluated. The primary objective was to assess progression-free survival (PFS). Secondary endpoints included overall survival (OS), treatment compliance, and safety, with a focus on the incidence and severity of immune-mediated adverse events (NCT04948411). Results: Thirty-one patients from seven centers were evaluated. Median follow-up was 50.3 months (95% CI: 48.6-54.4). Median PFS was 9.9 months (95% CI: 7.3-52.4), with a 36 month-PFS of 34.5% (95% CI: 17.7-52.1). Median OS was 34.9 months (95% CI: 26.0-NR), and the 36 month-OS was 46.3% (95% CI: 25.7-64.6). Durvalumab was administered for a median of 17 cycles (10 to 24), with 45.2% of patients completing the planned therapy. The main reason for discontinuation was disease progression. Treatment-related adverse events of any grade occurred in 12 patients (38.7%), with grade 3 events reported in two (6.5%). Pneumonitis was observed in 4 patients (12.9%) - grade 3 in 1 patient. Conclusions: PFS was lower in this analysis compared to the PACIFIC trial; however, OS was similar, indicating comparable efficacy in a real-world setting among Brazilian patients with unresectable stage III NSCLC. No new safety concerns were identified.